Human Keratinocyte Growth and Differentiation on Acellular Porcine Dermal Matrix in relation to Wound Healing Potential - Robert Zajicek; Vaclav Mandys; Ondrej Mestak; Jan Sevcik; Radana Königova; Eva Matouskova (The Scientific World Journal)
A number of implantable biomaterials derived from animal tissues are now used in modern surgery. Xe-Derma is a dry, sterile, acellular porcine dermis. It has a remarkable healing effect on burns and other wounds. Our hypothesis was that the natural biological structure of Xe-Derma plays an important role in keratinocyte proliferation and formation of epidermal architecture in vitro as well as in vivo. The bioactivity of Xe-Derma was studied by a cell culture assay. We analyzed growth and differentiation of human keratinocytes cultured in vitro on Xe-Derma, and we compared the results with formation of neoepidermis in the deep dermal wounds treated with Xe-Derma. Keratinocytes cultured on Xe-Derma submerged in the culture medium achieved confluence in 7–10 days. After lifting the cultures to the air-liquid interface, the keratinocytes were stratified and differentiated within one week, forming an epidermis with basal, spinous, granular, and stratum corneum layers. Immunohistochemical detection of high-molecular weight cytokeratins (HMW CKs), CD29, p63, and involucrin confirmed the similarity of organization and differentiation of the cultured epidermal cells to the normal epidermis. The results suggest that the firm natural structure of Xe-Derma stimulates proliferation and differentiation of human primary keratinocytes and by this way improves wound healing.